Case Report: Considerations of nocturnal ventilator support in ROHHAD syndrome in chronic care of childhood central hypoventilation with hypothalamus dysfunction - Zhao, Rui; Dong, Xiaosong; Gao, Zhancheng; Han, Fang (Frontiers in Pediatrics, 2022)
Rapid-onset obesity with hypothalamic dysfunction, hypoventilation, and autonomic dysregulation (ROHHAD) is a rare life-threatening disorder that can occur during childhood. All children with ROHHAD develop alveolar hypoventilation during wakefulness and sleep. The key treatment for these patients is the optimization of oxygenation and ventilation. Here, we report the case of a 5-year-old girl with suspected ROHHAD, with rapid weight gain, breathing cessation, decreased height, hypoventilation, central hypothyroidism, hyperprolactinemia, absolute deficiency of growth hormone, and negative PHOX2B sequencing results. The presentation met the diagnostic criteria for ROHHAD syndrome. During the 5-year follow-up, she presented with progressive deterioration of the function of the hypothalamus and respiratory center, hypoxemia (PO2 < 60 mmHg), and hypercapnia (transcutaneous carbon dioxide [TcPCO2] > 70 mmHg) during the first two cycles of N3 sleep with a poor response to ventilatory support. Early diagnosis and application of noninvasive positive pressure ventilation during sleep can improve the quality of life and outcomes of patients with ROHHAD, and polysomnography and TcPCO2 should be repeated every 3–6 months to follow the progress and regulate ventilator support. Multidisciplinary care is crucial for the successful management of these patients.